ANGAN PROGRAM APLIKASI SISTEM DISTRIBUSI DENGAN METODE SAVING MATRIX SEBAGAI DASAR KEPUTUSAN PEMBELIAN ARMADA (STUDI KASUS: PT KABELINDO MURNI TBK.) - Natalia, Christine; Dicky, Dicky (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
PT Kabelindo Murni Tbk. is a company involved in the industry of manufacturing electrical cable, telecommunication cable, and cable utilities. Nowadays, the company is implementing distribution system which is based on the partnership with the expedition company by using three kinds of transportations. The system is facing a problem where the transportation rental cost is high for each delivery to main distributors. This research proposes two new alternatives of distribution transportation system. The first alternative is to buy new batch of transportation for the company based on the currently rented transportation capacity. In the other hand, the second alternative is with route planning and rearrangement of delivery order of the current system. The use of company transportation is arranged with Saving Matrix, which is done with the goods weight and transportation volume. The proposed distribution system is done based on the minimum cost of both alternative systems. The result shows that the current transportation rental system has the lower cost compared to the first alternative with the total cost Rp 196.200.000,00. The cost difference between the first alternative of the current system with the second alternative is Rp 202.467.482,00. The chosen system is the second alternative, using the transportation rental service to deliver to four distributors in Jakarta, Bekasi, and Tangerang.